Identification and tracking of HTLV-1–infected T cell clones in virus-associated neurologic disease - Satoshi Nozuma; Eiji Matsuura; Masakazu Tanaka; Daisuke Kodama; Toshio Matsuzaki; Akiko Yoshimura; Yusuke Sakiyama; Shingo Nakahata; Kazuhiro Morishita; Yoshimi Enose-Akahata; Steven Jacoboson; Ryuji Kubota; et al. (JCI Insight, 2023)
Human T lymphotropic virus type 1–assoicated (HTLV-1–associated) myelopathy/tropical spastic paraparesis (HAM/TSP) is a neuroinflammatory disease caused by the persistent proliferation of HTLV-1–infected T cells. Here, we performed a T cell receptor (TCR) repertoire analysis focused on HTLV-1–infected cells to identify and track the infected T cell clones that are preserved in patients with HAM/TSP and migrate to the CNS. TCRβ repertoire analysis revealed higher clonal expansion in HTLV-1–infected cells compared with noninfected cells from patients with HAM/TSP and asymptomatic carriers (ACs). TCR clonality in HTLV-1–infected cells was similar in patients with HAM/TSP and ACs. Longitudinal analysis showed that the TCR repertoire signature in HTLV-1–infected cells remained stable, and highly expanded infected clones were preserved within each patient with HAM/TSP over years. Expanded HTLV-1–infected clones revealed different distributions between cerebrospinal fluid (CSF) and peripheral blood and were enriched in the CSF of patients with HAM/TSP. Cluster analysis showed similarity in TCRβ sequences in HTLV-1–infected cells, suggesting that they proliferate after common antigen stimulation. Our results indicate that exploring TCR repertoires of HTLV-1–infected cells can elucidate individual clonal dynamics and identify potential pathogenic clones expanded in the CNS.